2016
DOI: 10.1074/jbc.m116.731125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Human Plasminogen with Fibronectin-binding Protein B (FnBPB), a Fibrinogen/Fibronectin-binding Protein from Staphylococcus aureus

Abstract: Staphylococcus aureus is a commensal bacterium that has the ability to cause superficial and deep-seated infections. Like several other invasive pathogens, S. aureus can capture plasminogen from the human host where it can be converted to plasmin by host plasminogen activators or by endogenously expressed staphylokinase. This study demonstrates that sortase-anchored cell wall-associated proteins are responsible for capturing the bulk of bound plasminogen. Two cell wall-associated proteins, the fibrinogen-and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 58 publications
5
46
0
1
Order By: Relevance
“…To determine whether FnBPBs expressed by different strains of S. aureus also protected bacteria from the bactericidal effects of histones, the MBCs of H3 toward strains BH1CC (4), 8325-4 (42), and SH1000 (43) that express isoform I FnBPB and P1 (44) that expresses isoform IV FnBPB were very similar, although mutants lacking FnBPs (4,21,22,45) were ϳ3-fold more susceptible. This shows that both isoform I and isoform IV of FnBPB protect different strains of S. aureus to a similar degree despite isoform IV binding H3 less strongly than isoform I in vitro (Fig.…”
Section: Interactions Of Histones With S Aureus Fnbpbmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether FnBPBs expressed by different strains of S. aureus also protected bacteria from the bactericidal effects of histones, the MBCs of H3 toward strains BH1CC (4), 8325-4 (42), and SH1000 (43) that express isoform I FnBPB and P1 (44) that expresses isoform IV FnBPB were very similar, although mutants lacking FnBPs (4,21,22,45) were ϳ3-fold more susceptible. This shows that both isoform I and isoform IV of FnBPB protect different strains of S. aureus to a similar degree despite isoform IV binding H3 less strongly than isoform I in vitro (Fig.…”
Section: Interactions Of Histones With S Aureus Fnbpbmentioning
confidence: 99%
“…We previously showed that FnBPs expressed on the surface of S. aureus can capture PLG, which can be activated by PLG activators to cleave FBG (22). Hence, we investigated whether recombinant FnBPB could simultaneously bind PLG and histone H3.…”
Section: Activated Plasminogen Captured By Fnbpb Cleaves H3 and Enhanmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently in an another study, A region of FnBP_B has been shown to bind to both plasminogen and fg, and the dual ligand binding is independent to one another. 44…”
Section: Search For Conserved Domains In Sequence Databasesmentioning
confidence: 99%
“…MSCRAMMs usually have a multidomain organization and each domain can bind to a diverse array of host ligands. For example, the A domain of FnBPB (Fn-binding protein B) besides fibrinogen [14] recognizes and binds to elastin [15], plasminogen [16], and histones [16], while the C-terminal repetitive region interacts with Fn [17].…”
Section: Introductionmentioning
confidence: 99%